Evolution, importance and current perspectives for the teaching of English in Cuba. Its insertion in Latin American and Caribbean Educative Models (Mexico and Ecuador) - Vázquez Cedeño, Ana; González, MSc., Adrian Abreus (Revista Universidad de Guayaquil, 2011)
The research is addressed to highlight essential elements about the importance, evolution and perspectives of the current teaching-learning process of English in Cuba, putting an emphasis on higher education; as well as its insertion in the Educative Models of Mexico and Ecuador. In order to carry out the research project, theoretical foundation about the introduction of English teaching in the school curricula since elementary to advanced, and superior levels were taken into account. The research also provides elements related to the main challenges for the development of a teaching-learning process based on semi-attendance that the course “At Your Pace” proposes, so as the unders-tanding of practice as a fundamental element for the improvement of the process of foreign languages teaching that is developed nowadays.
Keywords: teaching-learning; method; semi-attendance; school curricula